Apologists on Trials: Justin’s Second Apology, the Literary Courtroom, and Pleading Philosophy - Corke-Webster, James (Zeitschrift für antikes Christentum, 2024)
This paper presents a fresh reading of Justin’s Second Apology . It focuses on that text’s narrative sections—the so-called martyrdom of Ptolemaeus and Lucius, and Justin’s own rift with Crescens. It demonstrates both these stories’ intratextual links, and their intertextual ties with contemporary mid-2d century literature—Achilles Tatius’ Greek novel Leucippe and Clitophon , and Apuleius’ Latin Apology . These in turn reveal the sophisticated rhetorical devices Justin employs, his goals in so doing, and the consequences for our understanding of the supposed new genre of Christian "apology."